PENGARUH SENIORITAS DAN LOYALITAS TERHADAP PROMOSI JABATAN PADA KARYAWAN DEALER MOBILTOYOTA (STUDI PADA PT. AGUNG AUTOMALL CABANG SUTOMO PEKANBARU) - Desmita, Lusia; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the influence of seniority and loyalty to promotion of position on Toyota car dealer employees at PT. Agung Automall Pekanbaru. The sampel in this study were taken 53 respondents and the technique used purposive sampling. The data in this study used survey method through quetionnaires falled by employees. The data obtained of questionnaire tested through SPSS16 program. The results of analysis used multiple linear regression analysis, determination test (R2), individual significance test (t test) and simultaneous significance test (F test) so it can be seen that seniority variable had a positive effect on promotion of position variable, seniority variable influences variable promotion of position , and a significant influence between seniority and loyalty variable promotion of position. The results shows R Square is the coefficient of determination and obtained R Square velue of 0,838. That is, seniority and loyalty effect promotion of position by 83,8%.\Keywords : Seniority,Loyalty and Promotion of Position